An evaluation of approaches used to teach quality improvement to pre-registration healthcare professionals: An integrative review. (August 2017) - Armstrong, Lorraine; Shepherd, Ashley; Harris, Fiona
Abstract: Background: Improving the quality of healthcare remains central to UK and international policy, practice and research. In 2003, The Institute of Medicine's ' Health Professions Education: A Bridge to Quality ', advocated quality improvement as a core competency for all healthcare professionals. As a result, developing capacity and capability of those applying improvement methodologies in the pre-registration population has risen, yet, little is known about the teaching approaches employed for this purpose. Objectives: To describe and analyse educational approaches used to teach quality improvement to pre-registration healthcare professionals and identify enabling and impeding factors. Design: Integrative review. Data sources: CINAHL, PsychINFO, MEDLINE, ERIC, ASSIA, SCOPUS and Google Scholar were accessed for papers published between 2000 and 2016. Review methods: Publications where quality improvement education was delivered to pre-registration healthcare professionals were eligible. One author independently screened papers, extracted data using a modified version of the Reporting of Primary Studies in Education Guideline and evaluated methodological quality using the Weight of Evidence Framework. The Kirkpatrick Education Evaluation Model was used to explore the impact of teaching approaches. Enabling and impeding factors were thematically analysed. A narrative synthesis of findings is presented. Results: Ten papers were included, representing nursing, pharmacy and medicine from UK, Norway and USA. Studies comprised four quantitative, four mixed method, one qualitative and one cluster randomised trial, all allocated medium Weight of Evidence. Teaching approaches included experiential learning cited in all studies, didactics in seven, group work in four, seminars in three, self-directed learning in three and simulation in one. Most studies measured Level 1 of the Kirkpatrick Model (reaction), all but one measured Level 2 (skills, knowledge or attitudes), none measured Level 3 (behaviour) and one measured Level 4 (patient outcomes). Enabling and impeding themes included: Teaching Approaches, Clinical/Faculty support, Information Provision, Curriculum Balance and Data. Conclusions: Evaluating quality improvement education is complex. Experiential learning combined with didactics is the favoured approach; however, attributing causality to educational intervention proves difficult in light of poor methodological rigour, lack of validated tools and complex clinical settings. Clarity regarding which quality improvement competencies are priority for this population would be useful to streamline future educational development and evaluation. Stronger collaboration between educators and clinicians is recommended to explore the multiple components and contextual factors associated with quality improvement education in practice. Ethnographic enquiry may be a logical next step to advance knowledge within the field.